The Life of Lam-ang. [anthology].
The theme of the epic revolves around the bravery and courage of the main character portrayed by Lam-ang, who was gifted with speech as early as his day of birth, who embarked on a series of adventures which culminated in his heroic death and subsequent resurrection. This series of adventures started with his search for his lost father who was murdered by the head-hunting Igorots in the Igorot country. While on his way, he met a certain Sumarang, whose name connotes obstruction, who tried to dissuade him from proceeding and who taunted him into a fight. The fight that ensued proved fatal to Sumarang as he was blown ?three kingdoms? away with a spear pierced through his stomach. This encounter led to another when he met a nine-headed serpent who, like Sumarang earlier tried to dissuade him from going any further. The serpent having been ignored challenged him into a fight which cost the serpent its heads. Lam-ang went on until he found it necessary to rest and take a short nap. While asleep, he dreamed of his father?s head being an object of festivities among the Igorots. He immediately arose and continued his journey until he found the Igorots indeed feasting over his father?s head. (Source: http://avrotor.blogspot.com/2012/11/life-of-lam-ang-biag-ni-lam-ang-anatomy.html)
Found in: Philippine Folk Literature : The Epics. (GR 325 P48 2001 v.8)
Keywords: Literature-Collections.